(untitled) (American Journal of Multidisciplinary Research and Innovation, 2024)
This study intended to measure the technical efficiency and sources of inefficiency for field pea producers in Ethiopia. The study used primary data collected from 207 smallholder farmers. A multi-stage sampling technique was followed to select sample households. A stochastic frontier was the model used, and a single-step estimation approach was followed. The result indicated that the mean technical efficiency is 49.23 %, and the average productivity of the crop is 0.96 tons/hectare. This indicates that the technical efficiency could be increased by 51.77 % through proper utilization of production variables, i.e. agrochemicals, oxen power, plot size, and seed rate. The inefficiency model result also confirmed that the technical inefficiency of field pea production was negatively affected by access to off-farm income, access to credit services, extension contacts, adoption of new technologies, access to training, and participation in contract farming of the crop. Therefore, this study recommends agricultural policies favoring vocational training to farmers on the new agricultural technology packages, availing access to off-farm incomes, facilitating credit services to farmers, and establishing legal frameworks that encourage contract farming.